A Learning of the Value of Popular Thai Songs based on the Ramayana Story - Wongsuwan, Nilobon; Bangchuad, Doungkamol (An Online Journal of Education, 2021)
This study aimed to analyze the value of songs containing content from the Thai literature in Ramayana story during 2007-2017. The method of selecting a purposive sampling of 6 songs by using Songs value analysis record form and in-depth interviews. Result of the study suggested that literary values include the use of idioms such as narrative, descriptive, comparison and illustration. Figure of speech including hyperbole, metaphor, simile, symbol and literary taste such as the taste of Thai literature and the taste of Sanskrit literature. Understanding of literary art will make the reader have a greater knowledge of the language and the ability to use the Thai language properly and gracefully. It is also being able to compose poetry or write stories interestingly.The content values include the meaning of the songs and the meaning of the royal writing in the Ramayana which include ethics as a code of conduct and morality. It is important to help sustaining and teach the readers of literature or listen to songs as courage, sacrifice, etc., and also recognize the importance of influential teaching from the past to the present such as unity and conscience. It also can make the readers or listeners have a way to live in normal society. The singing value such as singing technique, meaning expression and emotional expression. The visual arts values include content interpretation and presentation.